Analisis Efektivitas Penggunaan Media Sosial Instagram Dalam Peningkatan Penjualan Gold Drip Coffee Kemayoran Jakarta Pusat - Aprillianti, Diah; Yulianto, Yulianto; Hermansyah, Hermansyah (JAMBIS : Jurnal Administrasi Bisnis, 2024)
This research aims to analyze the effectiveness of business development in increasing sales of “Gold Drip Coffe in Kemayoran, Central Jakarta. The research method used in this study is a qualitative method. The research method used in this study is a qualitative method. The research data belongs to primary data obtained from observations, interviews, and documentation. The research findings indicate that using the social media platform Instagram as a business medium for Gold Drip Coffe is highly effective in boosting sales. This is attributed to Instagram’s ability to facilitate the promotion process with its wide reach and userfriendly features. To overcome obstacles and enhance sales, it is recommended to consistently create engaging content and utlize target insights.